Liquidity Relations, Current Ratio, Profitability, Gender Diversity, Company Size, and Company Value: Studies in Indonesia - Ummah, Dewi Roichatul; Yuliana, Indah (University of Merdeka Malang, 2023)
This study aims to test the influence of dependent variables (capital structure, current ratio, and profitability) on independent variables (company value) and test profitability moderation, gender diversity, and company size. Companies that use research data and are listed on the Indonesia Stock Exchange for the years 2017 through 2021 which are included in the research qualifications. Sourced from IDX website and company website. The results of the study found that the current ratio and profitability affect the value of the company. The size of the company negatively affects and the capital structure does not affect the value of the company. Profitability can strengthen the effect of the current ratio on company value and profitability cannot moderate the effect of capital structure on company value. Gender diversity can weaken the influence of capital structure and the current ratio to company value in a unidirectional manner. The influence of profitability on corporate values cannot be mitigated by gender diversity. The capital structure of the company can moderate its value depending on its size, which also has an impact on the company's value. The impact of the current ratio and profitability on the enterprise value cannot be mitigated by the company's size.